INHERITANCE PATTERN OF SOME QUALITATIVE TRAITS IN A CROSS BETWEEN CULTIVATED COWPEA (Vigna unguiculata (L.) Walp) AND A WILD RELATIVE - Awosanya, A. O. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study evaluated the inheritance patterns and segregation behaviour of five quantitative traits (flower weight, length/width ratio of terminal leaflet, number of days to first flowering, pod length and 100-seed weight) in populations derived from a cross between Ife BPC (Branched Peduncle Cowpea) and its wild relative (Vigna unguiculata subsp. Protrata). The cross was made at the screen house of the Department of Crop Protection and Environmental Biology, University of Ibadan, Ibadan, Nigeria. Each generation (P1, P2, F1, F2) was grown in experimental pots with standard spacing using completely randomized design. In this cross, populations with significant phenotypic and genetic variability for important agronomic traits were generated. The presence of transgressive segregants highlighted opportunity to select superior genotypes that combine traits from both parents. The F1 generation shows an intermediate mean pod length of 6.91cm, aligning closer to protracta than Ife BPC, suggesting partial dominance of the short-pod allele. The findings in this study are highly relevant for breeding programmes targeting traits associated with reproductive success, aesthetic value (e.g. in floriculture), or yield components in grain legumes where flower size may correlate with pod number or size. Future work should aim at confirming the genetic basis through molecular markers and mapping studies.